Putative Adult Neurogenesis in Old World Parrots: The Congo African Grey Parrot (Psittacus erithacus) and Timneh Grey Parrot (Psittacus timneh) - Mazengenya, Pedzisai; Bhagwandin, Adhil; Manger, Paul R.; Ihunwo, Amadi O. (Frontiers in Neuroanatomy, 2018)
In the current study, we examined for the first time, the potential for adult neurogenesis throughout the brain of the Congo African grey parrot (Psittacus erithacus) and Timneh grey parrot (Psittacus timneh) using immunohistochemistry for the endogenous markers proliferating cell nuclear antigen (PCNA), which labels proliferating cells, and doublecortin (DCX), which stains immature and migrating neurons. A similar distribution of PCNA and DCX immunoreactivity was found throughout the brain of the Congo African grey and Timneh grey parrots, but minor differences were also observed. In both species of parrots, PCNA and DCX immunoreactivity was observed in the olfactory bulbs, subventricular zone of the lateral wall of the lateral ventricle, telencephalic subdivisions of the pallium and subpallium, diencephalon, mesencephalon and the rhombencephalon. The olfactory bulb and telencephalic subdivisions exhibited a higher density of both PCNA and DCX immunoreactive cells than any other brain region. DCX immunoreactive staining was stronger in the telencephalon than in the subtelencephalic structures. There was evidence of proliferative hot spots in the dorsal and ventral poles of the lateral ventricle in the Congo African grey parrots at rostral levels, whereas only the dorsal accumulation of proliferating cells was observed in the Timneh grey parrot. In most pallial regions the density of PCNA and DCX stained cells increased from rostral to caudal levels with the densest staining in the nidopallium caudolaterale (NCL). The widespread distribution of PCNA and DCX in the brains of both parrot species suggest the importance of adult neurogenesis and neuronal plasticity during learning and adaptation to external environmental variations.